SHIP1 Activator AQX-1125 Regulates Osteogenesis and Osteoclastogenesis Through PI3K/Akt and NF-κb Signaling - Xie, Xudong; Hu, Liangcong; Mi, Bobin; Panayi, Adriana C.; Xue, Hang; Hu, Yiqiang; Liu, Guodong; Chen, Lang; Yan, Chenchen; Zha, Kangkang; Lin, Ze; Zhou, Wu; et al. (Frontiers in Cell and Developmental Biology, 2022)
With the worldwide aging population, the prevalence of osteoporosis is on the rise, particularly the number of postmenopausal women with the condition. However, the various adverse side effects associated with the currently available treatment options underscore the need to develop novel therapies. In this study, we investigated the use of AQX-1125, a novel clinical-stage activator of inositol phosphatase-1 (SHIP1), in ovariectomized (OVX) mice, identifying a protective role. We then found that the effect was likely due to increased osteogenesis and mineralization and decreased osteoclastogenesis caused by AQX-1125 in a time- and dose-dependent manner. The effect against OVX-induced bone loss was identified to be SHIP1-dependent as pretreatment of BMSCs and BMMs with SHIP1 RNAi could greatly diminish the osteoprotective effects. Furthermore, SHIP1 RNAi administration in vivo induced significant bone loss and decreased bone mass. Mechanistically, AQX-1125 upregulated the expression level and activity of SHIP1, followed upregulating the phosphorylation levels of PI3K and Akt to promote osteoblast-related gene expressions, including Alp, cbfa1, Col1a1, and osteocalcin (OCN). NF-κB signaling was also inhibited through suppression of the phosphorylation of IκBα and P65 induced by RANKL, resulting in diminished osteoclastogenesis. Taken together, our results demonstrate that AQX-1125 may be a promising candidate for preventing and treating bone loss.